The Nawa Gapura Marga Raja Gate as a Representation of the Cirebon Islamic Monarchy in Indonesia during the 17th Century - Kartasudjana, Tata; Abdillah, Fadhly (Universitas Pasundan, 2023)
Cirebon's early manuscripts, specifically Prince Wangsakerta's Pustaka Rajyarajya I Bhumi Nusantara, the Kingdom of Cirebon begins to expand its realm as Islam starts to flourish in Cirebon. It was reported that the Kings occupied a structure in the shape of a gate. In Cirebon, the kings were to take part in